Nematode Management in Sweet Potatoes (including Boniatos) - Zane Joseph Grabau; Joseph W Noling; Christopher Clark; Charles Overstreet (EDIS)
The primary intended audience of this publication is agricultural professionals involved in commercial sweet potato production directly or through advising roles (Extension agents, producers, crop consultants, academics, etc.). The purpose is to guide professionals in improving nematode management in sweet potato production and to give a concise but relatively comprehensive summary of relevant information to understand and manage nematodes in this crop in Florida.